Influence of Shoe Mass on Performance and Running Economy in Trained Runners - Rodrigo-Carranza, Víctor; González-Mohíno, Fernando; Santos-Concejero, Jordan; González-Ravé, Jose Maria (Frontiers in Physiology, 2020)
Purpose The aim of this study was to assess the effects of adding shoe mass on running economy (RE), gait characteristics, neuromuscular variables and performance in a group of trained runners. Methods Eleven trained runners (6 men and 5 women) completed four evaluation sessions separated by at least 7 days. The first session consisted of a maximal incremental test where the second ventilatory threshold (VT2) and the speed associated to the VO2max (vVO2max) were calculated. In the next sessions, RE at 75, 85, and 95% of the VT2 and the time to exhaustion (TTE) at vVO2max were assessed in three different shoe mass conditions (control, +50 g and +100 g) in a randomized, counterbalanced crossover design. Biomechanical and neuromuscular variables, blood lactate and energy expenditure were measured during the TTE test. Results RE worsened with the increment of shoe mass (Control vs. 100 g) at 85% (7.40%, 4.409 ± 0.29 and 4.735 ± 0.27 kJ⋅kg−1⋅km−1, p = 0.021) and 95% (10.21%, 4.298 ± 0.24 and 4.737 ± 0.45 kJ⋅kg−1⋅km−1, p = 0.005) of VT2. HR significantly increased with the addition of mass (50 g) at 75% of VT2 (p = 0.01) and at 75, 85, and 95% of VT2 (p = 0.035, 0.03, and 0.03, respectively) with the addition of 100 g. TTE was significantly longer (∼22%, ∼42 s, p = 0.002, ES = 0.149) in the Control condition vs. 100 g condition, but not between Control vs. 50 g (∼24 s, p = 0.094, ES = 0.068). Conclusion Overall, our findings suggest that adding 100 g per shoe impairs running economy and performance in trained runners without changes in gait characteristics or neuromuscular variables. These findings further support the use of light footwear to optimize running performance.